Helicobacter pylori From First Isolation to 2021 - Maria Roesler, Bruna (IntechOpen, 2021)
Helicobacter pylori is a universally distributed bacterium that affects more than half of the world population. H. pylori infection causes persistent inflammation with different clinical outcomes in humans, including chronic gastritis, peptic ulcer disease, and gastric cancer. The infection has also been associated with several extradigestive disorders. In this book, there is a comprehensive overview of contributors on H. pylori infection in diverse areas, including virulence factors of H. pylori and their importance for the clinical outcome of the diseases, discussions about the principal therapeutic regimens of bacterium eradication, also considering the antimicrobial resistance. H. pylori is clearly a very interesting bacterium and studies and discussions about its aspects are welcome to the medical and scientific communities.